Integrated Quantitative Proteomics and Metabolome Profiling Reveal MSMEG_6171 Overexpression Perturbing Lipid Metabolism of Mycobacterium smegmatis Leading to Increased Vancomycin Resistance - Zhuhua Wu (Frontiers in Microbiology, 2020)
In recent years, the treatment of tuberculosis is once again facing a severe situation because the existing antituberculosis drugs have become weaker and weaker with the emergence of drug-resistant Mycobacterium tuberculosis (Mtb). The studies of cell division and cell cycle-related factors in Mtb are particularly important for the development of new drugs with broad-spectrum effects. Mycobacterium smegmatis (Msm) has been used as a model organism to study the molecular, physiological, and drug-resistant mechanisms of Mtb. Bioinformatics analysis has predicted that MSMEG_6171 is a MinD-like protein of the septum site-determining protein family associated with cell division in Mycobacterium smegmatis. In our study, we use ultrastructural analysis, proteomics, metabolomics, and molecular biology techniques to comprehensively investigate the function of MSMEG_6171. Overexpression of MSMEG_6171 in Msm resulted in elongated cells, suggesting an important role of MSMEG_6171 in regulating cell wall morphology. The MSMEG_6171 overexpression could enhance the bacterial resistance to vancomycin, ethionamide, meropenem, and cefamandole. The MSMEG_6171 overexpression could alter the lipid metabolism of Msm to cause the changes on cellular biofilm property and function, which enhances bacterial resistance to antibiotics targeting cell wall synthesis. MSMEG_6171 could also induce the glyceride and phospholipid alteration in vivo to exhibit the pleiotropic phenotypes and various cellular responses. The results showed that amino acid R249 in MSMEG_6171 was a key site that can affect the level of bacterial drug resistance, suggesting that ATPase activity is required for function.